Correction of the FSHD myoblast differentiation defect by fusion with healthy myoblasts. Issue 1 (28th September 2015) - Dib, Carla; Saada, Yara Bou; Dmitriev, Petr; Richon, Catherine; Dessen, Philippe; Laoudj‐Chenivesse, Dalila; Carnac, Gilles; Lipinski, Marc; Vassetzky, Yegor S.
Abstract : Facioscapulohumeral dystrophy (FSHD) is a neuromuscular disease with a prevalence that could reach 1 in 8, 000 characterized by progressive asymmetric muscle weakness. Myoblasts isolated from FSHD muscles exhibit morphological differentiation defects and show a distinct transcription profile. These abnormalities may be linked to the muscle weakness in FSHD patients. We have tested whether fusion of FSHD myoblasts with primary myoblasts isolated from healthy individuals could correct the differentiation defects. Our results show that the number of hybrid myotubes with normal phenotype increased with the percentage of normal myoblasts initially cultured. We demonstrated that a minimum of 50% of normal nuclei is required for a phenotypic correction of the FSHD phenotype. Moreover, transcriptomic profiles of phenotypically corrected hybrid myotubes showed that the expression of deregulated genes in FSHD myotubes became almost normal. The number of deregulated pathways also decreased from 39 in FSHD myotubes to one in hybrid myotubes formed with 40% FSHD and 60% normal myoblasts. We thus propose that while phenotypical and functional correction of FSHD is feasible, it requires more than 50% of normal myoblasts, it creates limitations for cell therapy in the FSHD context. J. Cell. Physiol. 230: 62–71, 2016. © 2015 Wiley Periodicals, Inc.